Pagdating ng panahon. (Quezon City : Viva Video, 2002)
Lynette (Sharon Cuneta) is a conservative and religious lady who leads a boring life selling native delicacies in Laguna. She comes from a family of old maids. So when she gets a marriage proposal from Manuel (Robin Padilla), whose family is known to be a brood of chauvinists, she was ecstatic, Upon learning this news, Manuel's family was not exactly happy. But after Lynette figure in an accident, she starts to have a different outlook making her more confident prompting her to live a more exciting life that she starts to attract more attention from the male populace, leaving Manuel insecure. Meanwhile, Bubut (Rufa Mae Quinto) a common friend of Lynette and Manuel is secretly in love with Manuel and feels that she is the right girl for him. Withstanding her sister's advise, Lynette sets out to Manila as part of her business expansion, leaving Soni (Lynette sister), very disappointed. As she stays in Manila, she meets Joaquin, who is very fond of her. Manuel finds out about Joaquin and becomes jealous of him. But instead of returning his love, Lynette realizes how much she loves Manuel and she goes back home. Will Manuel accept Lynette still?